Ordinary management in the Agreste region of confections: A look at the daily life of women business owners in a shopping center - Souza, Denise Clementino de; Silva, Jéssica Pereira da; Siqueira, Juliette Ione Santana de (Contextus - Revista Contemporânea de Economia e Gestão, 2024)
Background: The clothing businesses in agreste region of Pernambuco originate from street markets and, even after relative modernization, the emergence of large shopping centers and the region's economic prominence, they retain practices based on ordinary management. It is in this context that women build their histories, managing their businesses surrounded by patriarchal relations, sexual division of labor and gender discrimination. In contrast, it is also in this environment that they reaffirm their inclusion, strength and persistence in the search for subsistence and equality in the job market. Purpose: This study sought to analyze the dynamics of ordinary management developed by women who own clothing businesses in a shopping center in the agreste region of ​​Pernambuco through a gender perspective. Method: Ten semi-structured interviews were carried out and the findings discussed based on thematic content analysis. Results: It was observed that the owners manage their businesses in a unique way based on the knowledge acquired in practice, without consolidated management tools, but that they are effective in achieving results in an ordinary way of managing; they continue to face the sexual division of labor; overloads of the double work journey; and other gender-related oppressions. Conclusions: The importance of clothing business for the personal and professional lives of these women is perceived, because through work they develop knowledge, gain certain recognition and economic emancipation.